The relationship of mothers' coping strategies and health behavior with oral health care for children. Issue 2 (August 2017) - Matsuo, Fumi; Sato, Shigemasa
Abstract: Objectives: In the Transactional Model of Stress and Coping, coping strategies and presence of social support influence health behavior. This study aimed to reveal relationships between mothers' coping styles, self-health behavior, children's oral health care, and social support from dental professionals. Methods: A total of 313 mothers participated in this study from all elementary schools in 2 cities in Japan. We classified participants into high and low groups with reference to self-health behavior and oral health care. To examine the associations of mother's coping styles, health behavior, and the presence of social support, logistic regression analysis was conducted. Results: There were significant differences in mother's coping styles associated with self-health behavior, oral health care, and presence of social support. In logistic regression analysis, the good self-health behavior group was more likely to use coping strategies of obtaining information and positive interpretation, to have fewer children, and less frequent use of avoidance-like thinking. The good oral health care group had a higher probability of obtaining information and using problem focused coping, and a lower probability of evading one's responsibility. Those who consulted dental offices used more positive interpretation, while mothers who did not consult dental offices used evading one's responsibility more frequently. Conclusions: Mother's coping styles had different associations with self-health behavior and children's oral health care. We may be able to use behavioral modification strategies effectively according to whether a mother consults with dental professionals. Future intervention studies based on this research are expected.